Assessment of Unmet Need for Contraception among eligible couples in Urban Slums of Raipur city of Chhattisgarh state - Verma, Nirmal; Bhawnani, Dhiraj; Soni, Gopal Prasad; Bandhi, Gayatri (Indian Journal of Community Health, 2014)
Background: India was the first country to launch National Family Planning Program in 1952. Even though various measures have been taken to encourage the usage of contraception but the achievement in this field was not to the extent expected due to various social and cultural factors. Objective: This study was planned to assess the prevalence and its determinants of unmet need for contraception among eligible couples in urban slums of Raipur city. Methodology: A cross sectional community based study was conducted using cluster sampling in urban slums of Raipur city from November 2011 to October 2012. During the study, 711 fecund married women, age group 15-49 years were included and predesigned and pretested proforma was used as a study tool. The obtained data were analyzed using appropriate statistical test. Results: Among all eligible married women 45 % were concentrated in the prime reproductive age 20-29 yrs. Majority of women were not educated. The total unmet need for family planning comes out to 32.9%. Age, Education, literacy, Occupation, Type of Family, No of living children, Birth Order , No of male child, No of female child , Husband literacy were the most significant predictor of unmet need. Conclusion: Percentage of unmet need is higher as compared to national data, so there is urgently need to ensure the same.